410 Endometrial cancer in young women: epidemiological features, therapeutic characteristics and prognosis. (18th September 2019) - Kaabia, O; Nourallah, G; Rym, Z; Aymen, L; Aymen, S; Mohamed, B; Hédi, K
Abstract : Objectives: The purpose of this study was to evaluate the epidemic profile and the survival rate of endometrial carcinoma in women ≤45 years of age in Tunisia Methods: It is a retrospective study of a prospective mono-centric database from January 2008 to January 2019. We evaluated the clinical history, treatment, and follow-up of 20 women ≤45 years of age diagnosed with endometrial cancer, from a global cohort of 228 patients diagnosed in our center with endometrial cancer during the same period. Results: The mean age was 40 years (29–45). Fifteen patients (75%) were married at the time of diagnosis and 12 (60%) were nulliparous. Menorragia was the main revealing symptom (60%). According to the FIGO classification for endometrial cancer: IA, 9 (45%); IB, 4 (20%). Tumors were well differentiated in 6 (30%), moderately differentiated in 5 (25%), and poorly differentiated in 9 (45%).A fertility-sparing technique was proposed in 9 cases (45%) and only one patient did not have hysterectomy. All patients had laparotomy when surgery was performed. External Radiotherapy was indicated in 25% of the patients and curitherapy in 10%.35% of the patients had chemotherapy. The mean overall survival (OS) was 104 months ±10. The OS and the disease free survival (DFS) at 3 and 5 years were equal, respectively at 95% and 80%. Conclusions: Patients ≤45 years of age with endometrial cancer represent less than 10% of all endometrial cancer patients. Although, advanced stage disease is prevalent (45%), the prognosis at 5 years seems acceptable (OS and DFS 80%).